Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Digging deeper into soil metagenomics: Opportunities and limitations for studying the genomic potential of soil bacteria and archaea - Itır Geydirici; Rubén Martínez-Cuesta; Sebastian Bibinger; Pamela Espíndola-Hernández; Silvia Gschwendtner; Natalia Rodríguez-Berbel; Stefanie Schulz; Ann-Christin Wicht; Michael Schloter (Biology and Fertility of Soils, 2026)
Soil microbial ecology has been transformed by recent progress in sequencing and metagenomics, reshaping our understanding of soil microbial functions. This article examines how metagenomics can be used to study the functional potential of soil microbiomes. We highlight opportunities and limitations of current tools and workflows utilized for the analyses of metagenomic sequencing data, providing guidance for methodological thoroughness and transparency, and emphasizing the need for standardized metadata, data availability and workflow reproducibility in metagenomic studies. We encourage authors to connect microbial functional potential to genomic context, functional redundancy and taxonomic diversity. By following these practices, the scientific community can ensure that soil metagenomics delivers robust, reproducible, and ecologically meaningful insights into the ‘living engine’ of fertile soils.